Preparation of photothermal responsive, antibacterial hydrogel by using PVA-Alg and silver nanofibers as building blocks - Ding, Jiaxin; Gao, Binbin; Mei, Xifan (Frontiers in Bioengineering and Biotechnology, 2023)
Abstract: Introduction: Photothermal responsive, antimicrobial hydrogels are very attractive and have great potential in the field of tissue engineering. The defective wound environment and metabolic abnormalities in diabetic skin would lead to bacterial infections. Therefore, multifunctional composites with antimicrobial properties are urgently needed to improve the current therapeutic outcomes of diabetic wounds. We prepared an injectable hydrogel loaded with silver nanofibers for efficient and sustained bactericidal activity. Methods: To construct this hydrogel with good antimicrobial activity, homogeneous silver nanofibers were first prepared by solvothermal method and then dispersed in PVA-lg solution. After homogeneous mixing and gelation, injectable hydrogels (Ag@H) wrapped with silver nanofibers were obtained. Results: By virtue of Ag nanofibers, Ag@H exhibited good photothermal conversion efficiency and good antibacterial activity against drug-resistant bacteria, while the in vivo antibacterial also showed excellent performance. The results of antibacterial experiments showed that Ag@H had significant bactericidal effects on MRSA and E. coli with 88.4% and 90.3% inhibition rates, respectively. Discussion: The above results indicate that Ag@H with photothermal reactivity and antibacterial activity is very promising for biomedical applications, such as wound healing and tissue engineering.